2014
DOI: 10.1038/aps.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant bupropion exerts alleviating properties in an ovariectomized osteoporotic rat model

Abstract: Aim: depression is a risk factor for impaired bone mass and micro-architecture, but several antidepressants were found to increase the incidence of osteoporotic fractures. in the present study we used ovariectomized (oVX) rats as a model of osteoporosis to investigate the effects of the antidepressant bupropion on the femoral bones. Methods: oVX animals were treated with bupropion (30, 60 mg·kg -1 ·d -1 ) for six weeks. bone turnover biomarkers (urinary dPd/Cr ratio, serum BALP, OC, TRAcP 5b, CTX and sRANKL le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 75 publications
6
8
0
Order By: Relevance
“…Pro-infammatory cytokines (IL-1β, IL-6, IL-8 and TNF-α) play an important role in regulating bone resorption, while estrogen deficiency always leads to remarkable increase in pro-iflammatory cytokines [ 2 ]. In the study, the serum levels of IL-1β and TNF-α were much higher in OVX group, which is consistent with other studies [ 40 , 41 ]. EA has been shown to display an anti-inflammatory effect in different models of chronic inflammation in mice through the down-regulation of pro-inflammatory cytokines such as IL-1β, IL-18, TNF-α [ 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Pro-infammatory cytokines (IL-1β, IL-6, IL-8 and TNF-α) play an important role in regulating bone resorption, while estrogen deficiency always leads to remarkable increase in pro-iflammatory cytokines [ 2 ]. In the study, the serum levels of IL-1β and TNF-α were much higher in OVX group, which is consistent with other studies [ 40 , 41 ]. EA has been shown to display an anti-inflammatory effect in different models of chronic inflammation in mice through the down-regulation of pro-inflammatory cytokines such as IL-1β, IL-18, TNF-α [ 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Besides, TRAP is a representative enzyme of osteoclast marker . Previous studies have demonstrated that serum levels of the bone resorption biomarkers, such as BLAP, OC, TRAP, and CTX, were significantly elevated in the OVX group compared to the sham operated group . Our studies revealed that AG490 promoted OVX‐induced increase in the osteocalcin, ALP, BALP, TRAP, and CTX‐I levels.…”
Section: Discussionsupporting
confidence: 59%
“…In OVX rats, a significant increase of serum and bone ALP, OCN and TRACP have been recorded [22, 23]. ALP and TRACP are respectively secreted by osteoblasts and osteoclasts, ALP is essential for bone mineralization while TRACP, especially TRACP-5b, is correlates with resorptive activity [24, 25].…”
Section: Discussionmentioning
confidence: 99%